Banana Peel Bar: An Effective Nutritional Supplement - Bagade, Sakshi Dhananjay; Handal, Priya Babasaheb; Lobo, Christopher Benjamin; Shinde, Sanket Pandurang (Journal of Drug Delivery and Therapeutics, 2025)
Every year a lot of kitchen waste is generated, mainly fruit and vegetable peels. The increasing population increases the demand for raw materials and thus impact the generation of this waste. The large amount of waste gets dumped into dumping grounds, causing various airborne and waterborne diseases. The peels of vegetables and fruits can result as nutritional components of food or medicinal components of pharmaceutical products, as they contain various phytochemicals and nutrients. This research looks upon such a beneficial and cost-effective element that is Banana peels. Banana peels have been used since ancient times due to their soothing, anti-inflammatory, and fibre-rich properties. Banana peel is the core component of our nutritive bar along with various beneficial components like dates, rice flakes, germinated wheat, magaj (Watermelon seeds), and charoli seeds (Cuddapah almond) which provide an additional and balanced nutrient value to our nutritive bar. Why a nutritive bar? Nutritive bars are a balanced source of nutrients that fills the satiety and are also cost-effective so that the common man can affordably purchase them. Keywords: Banana peel, Nutritive bar, Nutrition supplement, Fruit waste, Peel bar.